2018
DOI: 10.3390/cells7120254
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Protein Synthesis by eIF2α Phosphorylation Protects Cell from Heat Stress-Mediated Apoptosis

Abstract: Global warming poses a considerable threat to human health, necessitating a proper understanding of mechanisms underlying cell death in the pathogenesis of heat-related diseases. Although mechanisms governing cytoplasmic response to heat are well understood, processes regulating cellular response to disruption of proteostasis in the endoplasmic reticulum (ER) due to heat stress remain unclear. The current study reveals that hyperthermic conditions may lead to a disturbance of ER homeostasis, also known as ER s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…It is generally accepted that decreased protein synthesis is critical to protect cells from stress [45,46]. Importantly, we showed that translational attenuation upon heat stress was crucial to protect cells [22]. Based on these results, we hypothesized that the attenuation of protein synthesis by PERK-mediated eIF2α phosphorylation might be required to protect neuronal cells against chronic heat stress in vivo.…”
Section: Attenuation Of Protein Synthesis By Eif2α Phosphorylation Wamentioning
confidence: 56%
See 3 more Smart Citations
“…It is generally accepted that decreased protein synthesis is critical to protect cells from stress [45,46]. Importantly, we showed that translational attenuation upon heat stress was crucial to protect cells [22]. Based on these results, we hypothesized that the attenuation of protein synthesis by PERK-mediated eIF2α phosphorylation might be required to protect neuronal cells against chronic heat stress in vivo.…”
Section: Attenuation Of Protein Synthesis By Eif2α Phosphorylation Wamentioning
confidence: 56%
“…We previously showed that heat exposure caused a disturbance in proteostasis not only in the cytosol but also in the ER, and it subsequently induced UPR signaling in mouse embryo fibroblasts (MEFs) [22]. Although several studies showed the hyperthermal effect on Drosophila and mice [30,31], there has been no research on how heat stress is correlated with ER stress in vivo.…”
Section: Heat Stress Induced Er Stress and The Upr In Drosophilamentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is worth noting that most stress conditions, such as deficiency of growth factors, heat shock, and ER stress, also leads to disruption of the activity of the eIF2 initiating factor by phosphorylation of its α subunit. Phosphorylation eIF2α results in the formation of a stable eIF2-GDP complex with eIF2B, which strongly reduces the ability to exchange nucleotides guanine by eIF2B [53,54]. And it has been demonstrated that down-regulation of PERK-eIF2α-ATF4-CHOP pathway inhibits ER stress-mediated apoptosis [55].…”
Section: Discussionmentioning
confidence: 99%